Inspection of aircraft wing panels using unmanned aerial vehicles - Malandrakis, Konstantinos; Savvaris, Al; Gonzalez Domingo, Jose Angel; Avdelidis, Nicolas Peter; Tsilivis, Panagiotis; Plumacker, Florence; Zanotti Fragonara, Luca; Tsourdos, Antonios (IEEE, 2018)
In large civil aircraft manufacturing a time-consuming post-production process is the non-destructive inspection of wing panels. This work aims to address this challenge and improve the defects' detection by performing automated aerial inspection using a small off-the-shelf multirotor. The UAV is equipped with a wide field-of-view camera and an ultraviolet torch for implementing non-invasive imaging inspection. In particular, the UAV is programmed to perform the complete mission and stream video, in real-time, to the ground control station where the defects' detection algorithm is executed. The proposed platform was mathematically modelled in MATLAB/SIMULINK in order to assess the behaviour of the system using a path following method during the aircraft wing inspection. The UAV was tested in the lab where a six-meter-long wing panel was one-side inspected. Initial results indicate that this inspection method could reduce significantly the inspection time, cost, and workload, whilst potentially increasing the probability of detection.